2005
DOI: 10.1074/jbc.m409652200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanistic Studies of Escherichia coli Nitroreductase with the Antibiotic Nitrofurazone

Abstract: The antibiotics nitrofurazone and nitrofurantoin are used in the treatment of genitourinary infections and as topical antibacterial agents. Their action is dependent upon activation by bacterial nitroreductase flavoproteins, including the Escherichia coli nitroreductase (NTR). Here we show that the products of reduction of these antibiotics by NTR are the hydroxylamine derivatives. We show that the reduction of nitrosoaromatics is enzyme-catalyzed, with a specificity constant ϳ10,000-fold greater than that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
243
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(288 citation statements)
references
References 31 publications
19
243
1
4
Order By: Relevance
“…NfsB is a homodimeric flavoenzyme which can use either NADH or NADPH to reduce the tightly bound FMN; after dissociation of the NAD (P) þ ; a variety of nitroaromatic or quinone substrates can be reduced in a second reaction step Lovering et al, 2001;Race et al, 2005). The published K m for NfsB nitroreductase with CB1954 is 862 mM , which is considerably higher than its peak serum concentration achievable in humans (5 -10 mM) (Chung-Faye et al, 2001).…”
mentioning
confidence: 99%
“…NfsB is a homodimeric flavoenzyme which can use either NADH or NADPH to reduce the tightly bound FMN; after dissociation of the NAD (P) þ ; a variety of nitroaromatic or quinone substrates can be reduced in a second reaction step Lovering et al, 2001;Race et al, 2005). The published K m for NfsB nitroreductase with CB1954 is 862 mM , which is considerably higher than its peak serum concentration achievable in humans (5 -10 mM) (Chung-Faye et al, 2001).…”
mentioning
confidence: 99%
“…The structure of the active site of paMdaB (Fig 7B) is very similar to that of paAzoR1 (Fig 4A), it is a predominantly hydrophobic pocket surrounded by aromatic residues. In paMdaB Thr87 is in a similar position to Phe60 in paAzoR1 which has previously been identified to be important for determining substrate specificity of azoreductases [42]. In a model of paAzor3 it was suggested that the equivalent residue (Thr60), due to its strategic position at one of the entrances to the active site, would determine the accessibility to the active site for larger substrates [19].…”
Section: Nad(p)h Quinone Oxidoreductase Activitymentioning
confidence: 95%
“…The crystallized structures of nitrofurazone and 2'-hydroxy-4''-dimethylamino-chalcone were retrieved from the Brookhaven Protein Data Bank (PDB entry code 1yki, resolution at 1.70 Å; Race et al, 2005) and file ob1067.cif (resolution at 1.01 Å; Liu et al, 2002), respectively, and were used as geometry references in the building up of all ligands. Crystallographic information of a nitrothiophene 2-carbaldehyde was retrieved from the file lh6379.cif (resolution at 1.18 Å; McBurney et al, 2005) and also used as a reference particularly in the construction of the nitrothiophene ring moiety.…”
Section: Methodsmentioning
confidence: 99%